Concise encyclopedia of chemical technology : Kirk-Othmer. (Hoboken : Wiley, 2007)
The fifth edition of the Kirk-Othmer Encyclopedia of Chemical Technology builds upon the solid foundation of the previous editions, which have proven to be a mainstay for chemists, biochemists, and engineers at academic, industrial, and government institutions since publication of the first edition in 1949. The new edition includes necessary adjustments and modernization of the content to reflect changes and developments in chemical technology.
Keywords: Chemische technologie